In-Vitro Susceptibility of Mycobacterium Tuberculosis to Extracts of Uvaria Afzelli Scott Elliot and Tetracera Alnifolia Willd (2011)
Tuberculosis is a global burden with one –third of the world’s population infected with the pathogen Mycobacterium tuberculosis and an annual 2 million deaths from the disease. This high incidence of infection and the increased rate of resistant strains of the organism (MDR- and XDR- TB) have called for an urgent need to develop new anti-tuberculosis drugs from plants. The crude extract of Uvaria afzelli Scott Elliot (Annonaceae) root bark, and leaves and root bark of Tetracera alnifolia Willd. (Dilleniaceae) were investigated for anti-Mycobacterium tuberculosis activity using the MABA assay method. Anti- Mtb activity was determined against Mtb H37RvATCC 27294 at concentrations of 100- 0.390μg/mL. The hexane and chloroform extracts of the root bark of Tetracera alnifolia and the chloroform extract of Uvaria afzelli had anti- Mtb activity with MIC <100 μg/mL. Phytochemical screening for secondary metabolites revealed the presence of tannins, triterpenoid saponins, cardiac glycoside and alkaloids. The anti- Mtb activity demonstrated by the crude extracts is attributed to the presence of tannins and other secondary metabolites which are known to have strong antimicrobial activity. The results therefore support the local use of Uvaria afzelli and Tetracera alnifolia in the treatment of cough associated with tuberculosis and other microbial infections of the respiratory tract and suggest that these plants may be of therapeutic importance in the treatment of tuberculosis.